Kinetics of Lipoprotein(a) in patients undergoing weekly lipoprotein apheresis for Lp(a) hyperlipoproteinemia. (November 2017) - Tselmin, S.; Müller, G.; Schatz, U.; Julius, U.; Bornstein, S.R.; Hohenstein, B.
Abstract: Introduction: Lipoprotein apheresis (LA) represents the only effective therapeutic option for patients with elevated Lipoprotein(a) (Lp(a)) levels. We aimed at analyzing the Lp(a) reduction, rebound rates as well as mean interval values between two weekly apheresis sessions, since this might be important for the prediction of the residual cardiovascular risk and development of individualized approaches for this special therapeutic strategy. Materials and methods: 20 patients under weekly and 2 patients under twice weekly apheresis were included. We measured serum concentrations of Lp(a), total, LDL-, HDL - cholesterol and triglycerides daily over 7 days after single LA sessions. Results: Mean Lp(a) levels was 158.1 ± 69.82 nmol/l before the LA session, decreased acutely by 76 ± 7% and increased to 97 ± 13% of the baseline value within 7 days in patients under weekly treatment. By mathematical modeling, the acute Lp(a) reduction can be calculated from the function: y (nmol/l) = 3.415 + 0.738 * x (R 2  = 0.970), where x is the baseline Lp(a) value. The recovery rate can be predicted from the equation: y (%) = 22.49 + 18.64 * x – 1.14 * x 2 (R 2  = 0.874), where x is the day after apheresis. The empirical formula for the mean interval value is: y (nmol/l) = x − 12, where x is the absolute reduction in nmol/l. Conclusion: We modeled − for the first time − equations to predict the course of Lp(a) serum levels under weekly LA which are simple, reliable and enable the development of optimal individualized protocols of this costly lipid lowering therapy.